2023
DOI: 10.1146/annurev-ento-120220-113618
|View full text |Cite
|
Sign up to set email alerts
|

Postcopulatory Behavior of Tephritid Flies

Abstract: Mating produces profound changes in the behavior of female flies, such as an increase in oviposition, reduction in sexual receptivity, increase in feeding, and even excretion. Many of these changes are produced by copulation, sperm, and accessory gland products that males transfer to females during mating. Our knowledge on the function of the male ejaculate and its effect on female insects is still incipient. In this article, we review peri- and postcopulatory behaviors in tephritid flies. We address the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 157 publications
0
8
0
Order By: Relevance
“…The filiform shape of the male tract, with no ejaculatory bulb, is in favour of a continuous sperm transfer during copulation instead of a time‐limited ejaculation. In that case, the duration of copulation may allow regulation of sperm transfer, as in some tephridid flies (Perez‐Staples & Abraham, 2023). In BSF it is from 20 to 40 min (Giunti et al, 2018), indicating variability, but not in the same order of magnitude as sperm stocks in females.…”
Section: Discussionmentioning
confidence: 99%
“…The filiform shape of the male tract, with no ejaculatory bulb, is in favour of a continuous sperm transfer during copulation instead of a time‐limited ejaculation. In that case, the duration of copulation may allow regulation of sperm transfer, as in some tephridid flies (Perez‐Staples & Abraham, 2023). In BSF it is from 20 to 40 min (Giunti et al, 2018), indicating variability, but not in the same order of magnitude as sperm stocks in females.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous factors influence fruit fly mating, and mating has different effects on fruit flies. For example, mating induces profound changes in female fly behavior, such as increased oviposition, decreased sexual receptivity, and effects on offspring hatching 140 . Bactrocera pyrifoliae undergoes multiple generations of inbreeding, and offspring hatching might be inhibited 141 .…”
Section: Tephritidae Reproductive Processesmentioning
confidence: 99%
“…Recently, Pogue et al (2022)have shown that female mating propensity reduces over time [59]: with an average of 75% females C.capitata re-mating a second time but only less than 25% performing successive re-mating. The litterature on medfly remating varies with studies and the global picture is not yet complete, as reviewed by Pérez-Staple & Abraham [60]. Here, we've chosen to estimate the parameters δ and δ S based on the values reported from laboratory experiments by [30,Table 1].…”
Section: Parameterization and Simulationsmentioning
confidence: 99%